The cost-effectiveness of once-weekly semaglutide compared with other GLP-1 receptor agonists in type 2 Diabetes: a systematic literature review. (4th March 2021) - Ruan, Zhen; Yang, Lisong; Shi, Honghao; Yue, Xiaomeng; Wang, Yao; Liang, Miaoying; Hu, Hao
ABSTRACT: Introduction : As a novel glucagon-like peptide-1receptor agonist (GLP-1 RA) for type 2 diabetes (T2D) treatment, the economic value of once-weekly semaglutide had been assessed in several country settings. The authors' objective was to systematically review the existing pharmacoeconomic literature evaluating the cost-effectiveness associated with once-weekly semaglutide compared with other GLP-1 RAs and provide implications for further researches. Areas covered : We conducted a systematic literature review of cost-effectiveness analysis (CEA) published up to 25 July 2020 in PubMed, web of science, and the ISPOR presentation database, compared once-weekly semaglutide with other GLP-1 RAs in T2D. Nineteen studies were identified, including 8 short-term and 11 long-term studies. General characteristics and main results of the included studies were summarized. Expert opinion : This review provided references for other countries to overview the value of once-weekly semaglutide compared with other GLP-1 RAs in T2D in the healthcare decision-making process and to conduct their CEA studies associated with once-weekly semaglutide. The authors found that the cardiovascular (CV) benefit of once-weekly semaglutide was under-estimated in current studies and suggested that the methods of economic evaluations for novel anti-diabetic drugs with CV benefit should be improved in future researches.